2019
DOI: 10.3390/ani9080567
|View full text |Cite
|
Sign up to set email alerts
|

Lactational Responses of Heat-Stressed Dairy Goats to Dietary L-Carnitine Supplementation

Abstract: Heat stress causes significant losses in milk production, and nutritional strategies are needed to alleviate its effects. Endogenous carnitine synthesis is also reduced by heat stress (HS). Carnitine plays a central role in fatty acid oxidation and buffers the toxic effects of acyl groups. We hypothesized that carnitine supplementation would make up for any carnitine deficiencies during HS and improve lipid metabolism. The objective was to evaluate rumen-protected L-carnitine (CAR) supplementation in dairy goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 28 publications
12
25
1
Order By: Relevance
“…For TN goats, average rectal temperature and respiratory rate values increased ( p < 0.05) from 38.74 °C and 28 breaths/min at 08:00 h to 39.00 °C and 33 breaths/min at 12:00 h. No additional increase was observed at 17:00 h for TN goats (39.10 °C and 35 breaths/min). These results agree with the findings of Hamzaoui et al [ 1 ], Mehaba et al [ 6 ], and Contreras-Jodar et al [ 9 ], where goats exposed to HS experienced high rectal temperatures and respiratory rates. The increment in respiratory rate under HS conditions was for dissipating the heat load by pulmonary water evaporation as indicated by the greater consumption of water by HS goats (see hereafter).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…For TN goats, average rectal temperature and respiratory rate values increased ( p < 0.05) from 38.74 °C and 28 breaths/min at 08:00 h to 39.00 °C and 33 breaths/min at 12:00 h. No additional increase was observed at 17:00 h for TN goats (39.10 °C and 35 breaths/min). These results agree with the findings of Hamzaoui et al [ 1 ], Mehaba et al [ 6 ], and Contreras-Jodar et al [ 9 ], where goats exposed to HS experienced high rectal temperatures and respiratory rates. The increment in respiratory rate under HS conditions was for dissipating the heat load by pulmonary water evaporation as indicated by the greater consumption of water by HS goats (see hereafter).…”
Section: Resultssupporting
confidence: 93%
“…The BW change, DM intake, water consumption, and calculated energy balance data of TN and HS goats with or without PG supplementation are shown in Table 2 . The decrease ( p < 0.01) in DM intake by the effect of HS was 34% on average, which is similar to DM intake losses in heat-stressed goats at mid lactation (–26%; [ 6 ]), but greater than losses observed during late lactation (–19%; [ 1 ]). Heat-stressed animals decrease their DM intake to reduce the production of metabolic heat given the fact that heat increment of feeding is an important source of heat production in ruminants [ 23 ].…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Throughout the experiment, goats were individually kept in sawdust-bedded pens (1.0 × 1.5 m) equipped with individual feeders and drinkers. Since there are no studies reported in the literature examining the impact of cold temperatures in Murciano-Granadina goats, power analysis was performed based on data reported in heat-stressed goats of the same breed and use the same experimental design and facilities [ 21 , 22 ]. The fat-corrected milk data recorded for control and heat stress goats (2.10 vs. 1.78, SD = 0.22, respectively) were used to calculate the anticipated number of goats needed to provide sufficient statistical power.…”
Section: Methodsmentioning
confidence: 99%